The Impact of Pile Diameter on the Performance of Single Piles: A Kinematic Analysis Based on the TBEC 2018 Guidelines - Mehmet Hayrullah Akyıldız; Mehmet Salih Keskin; Senem Yılmaz Çetin; Sabahattin Kaplan; Gültekin Aktaş (Buildings)
This study investigates the effect of pile diameter on the seismic performance of single piles using the kinematic interaction framework outlined in Method III of the Turkish Building Earthquake Code TBEC-2018. Pile diameters of 65 cm, 80 cm, and 100 cm were analyzed under four different soil profiles—soft clay, stiff clay, very loose sand-A, and very loose sand-B. The methodology integrated nonlinear spring modeling (P-y, T-z, Q-z) for soil behavior, one-dimensional site response analysis using DEEPSOIL, and structural analysis with SAP2000. The simulation results showed that increasing the pile diameter led to a significant rise in internal forces: the maximum bending moment increased up to 4.0 times, and the maximum shear force increased 4.5 times from the smallest to the largest pile diameter. Horizontal displacements remained nearly constant, whereas vertical displacements decreased by almost 50%, indicating improved pile–soil stiffness interaction. The depth of the maximum moment shifted according to the soil stiffness, and stress concentrations were observed at the interfaces of stratified layers. The findings underline the importance of considering pile geometry and soil layering in seismic design. This study provides quantitative insights into the trade-off between displacement control and force demand in seismic pile design, contributing to safer foundation strategies in earthquake-prone regions.